PENGARUH MODEL CONCEPTUAL CHANGE BERBANTUAN VIDEO INTERAKTIF TERHADAP PENINGKATAN PEMAHAMAN KONSEP SISWA PADA MATERI PERUBAHAN IKLIM DI SEKOLAH DASAR - Amelia Sapitrii; Dewi Fitriani; Siti Aisyah; Rahmatika Layyinah; Regina Adeliani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the effect of the Conceptual Change model assisted by interactive video on improving students' conceptual understanding of climate change material in class IV of SD Negeri Cilangla. This research was motivated by the low absorption of essential material by students, which was worsened by the emergence of misconceptions and low student activity in the classroom. This research uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research subjects consisted of 50 students, divided into an experimental class and a control class, each with 25 students. Data were collected using a conceptual understanding test and analyzed through normality tests, homogeneity tests, independent sample t-tests, and N-gain tests. The results showed that the data were normally and homogeneously distributed. The independent sample t-test obtained a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant effect of using the Conceptual Change model assisted by interactive video on improving students' conceptual understanding. The N-gain test results showed that the experimental class average was 77.28% (effective), higher than the control class at 41.12% (less effective). Thus, the Conceptual Change model assisted by interactive video is effective in improving students' conceptual understanding of climate change material in elementary schools.